Exploring residents' perceptions of the social impacts of tourism on the Sunshine Coast, Australia - Sharma, B.; Dyer, P.; Carter, J.; Gursoy, D (Routledge, 2008)
This study identified residents' perceptions of major social impacts from tourism and their social concerns. A survey of households on the Sunshine Coast region covering the hinterland residential, hinterland high tourist activity, coastal residential and coastal high tourist activity areas of the three shires (Caloundra City Council, Maroochy Shire and Noosa Shire) was carried out to assess residents' perceptions of social impacts. Altogether 732 responses were received. Based on the perceptions of the respondents, the survey results suggest that if rates of resident perceptions are aligned with actual impact, tourism has the highest impact on traffic congestion. Residents perceived that the opportunity to meet people from other regions of the world provides a valuable experience for respondents to better understand their culture and society. The study also found a number of significant correlations between residents' concerns and tourism impact variables. It revealed that the principal area of concern was the lack of capacity of roads and transportation followed by perceived negative impacts on the surrounding environment and crime related incidents.